B-Lymphocyte Signalling Abnormalities and Lupus Immunopathology. (1st August 2013) - Taher, Taher E.; Muhammad, Hawzheen A.; Bariller, Edwige; Flores-Borja, Fabian; Renaudineau, Yves; Isenberg, David A.; Mageed, Rizgar A.
Abstract : Lupus is a complex autoimmune rheumatic disease of unknown aetiology. The disease is associated with diverse features of immunological abnormality in which B-lymphocytes play a central role. However, the cause of atypical B-lymphocyte responses remains unclear. In this article, we provide a synopsis of current knowledge on intracellular signalling abnormalities in B-lymphocytes in lupus and their potential effects on the response of these cells in mouse models and in patients. There are numerous reported defects in the regulation of intracellular signalling proteins and pathways in B-lymphocytes in lupus that, potentially, affect critical biological responses. Most of the evidence for these defects comes from studies of disease models and genetically engineered mice. However, there is also increasing evidence from studying B-lymphocytes from patients and from genome-wide linkage analyses for parallel defects to those observed in mice. These studies provide molecular and genetic explanations for the key immunological abnormalities associated with lupus. Most of the new information appears to relate to defects in intracellular signalling that impact B-lymphocyte tolerance, cytokine production and responses to infections. Some of these abnormalities will be discussed within the context of disease pathogenesis.